Collected Poems, Veronica Forrest-Thomson, Anthony Barnett (ed.) (2008)Selected Poems: Language–Games, On the Periphery and Other Writings, Veronica Forrest-Thomson, Anthony Barnett (ed.) (2000)Poetic Artifice: A Theory of Twentieth-Century Poetry, Veronica Forrest-Thomson (1978)Poetic Artifice: A Theory of Twentieth-Century Poetry, Veronica Forrest-Thomson, Gareth Farmer (ed.) (2016). Issue 2 (27th February 2023) - Wheale, Nigel
Review of: Collected Poems, Veronica Forrest-Thomson, Anthony Barnett (ed.) (2008) Bristol: Shearsman Books in association with Allardyce Books, 188 pp., ISBN 978-1-90570-080-6, p/bk, £12.95   Selected Poems: Language–Games, On the Periphery and Other Writings, Veronica Forrest-Thomson, Anthony Barnett (ed.) (2000) London: Invisible Books, 130 pp., ISBN 978-0-95328-261-6, p/bk, £23.00   Poetic Artifice: A Theory of Twentieth-Century Poetry, Veronica Forrest-Thomson (1978) Manchester: Manchester University Press, 262 pp., ISBN 978-1-84861-445-1, p/bk, £15.49   Poetic Artifice: A Theory of Twentieth-Century Poetry, Veronica Forrest-Thomson, Gareth Farmer (ed.) (2016) Swindon: Shearsman Books, 238 pp., ISBN 978-1-84861-445-1, h/bk, £25.00